2008
DOI: 10.1073/pnas.0712316105
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ oscillation frequency decoding in cardiac cell hypertrophy: Role of calcineurin/NFAT as Ca 2+ signal integrators

Abstract: The role of Ca 2؉ signaling in triggering hypertrophy was investigated in neonatal rat cardiomyocytes in vitro. We show that an increase in cell size and sarcomere reorganization were elicited by receptor agonists such as Angiotensin II, aldosterone, and norepinephrine and by a small rise in medium KCl concentration, a treatment devoid of direct effects on receptor functions. All these treatments increased the frequency of spontaneous [Ca 2؉ ] transients, caused nuclear translocation of transfected NFAT(GFP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 39 publications
9
91
2
1
Order By: Relevance
“…In excitable cardiomyocytes, increases in the frequency or amplitude of Ca 2ϩ transients evoked by Ca 2ϩ influx-induced Ca 2ϩ release have been suggested to encode signals for induction of hypertrophy (9). A partial depolarization of plasma membrane by receptor stimulation is reported to increase the frequency of Ca 2ϩ oscillations, leading to activation of nuclear factor of activated T cells (NFAT), a transcription factor that is predominantly regulated by calcineurin (10). Recent reports have indicated that transient receptor potential canonical (TRPC) subfamily proteins play an essential role in agonistinduced membrane depolarization (11,12).…”
mentioning
confidence: 99%
“…In excitable cardiomyocytes, increases in the frequency or amplitude of Ca 2ϩ transients evoked by Ca 2ϩ influx-induced Ca 2ϩ release have been suggested to encode signals for induction of hypertrophy (9). A partial depolarization of plasma membrane by receptor stimulation is reported to increase the frequency of Ca 2ϩ oscillations, leading to activation of nuclear factor of activated T cells (NFAT), a transcription factor that is predominantly regulated by calcineurin (10). Recent reports have indicated that transient receptor potential canonical (TRPC) subfamily proteins play an essential role in agonistinduced membrane depolarization (11,12).…”
mentioning
confidence: 99%
“…Model developments: Based on the published experimental results [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] , we approximately consider, BF in SR, cells or extra-cells, as quasi liquid plasmas in physics, the plasmas are quasi neutral electromagnetically; biological or biochemical components such as free Ca++ in BF, SR SubMembrane (SRSM) or Cell Membrane (CM), Ca++H+ (Ca++ or Na+K+) ATPases, NCX, Ca++ carriers and myosin heads, because disturbances, internal excitations or external stimulations always exist, often are displaced from their equilibrium positions or distances, the redistribution of charges and masses will respectively set up forces, tensions or pressures at the components. The forces, the tensions or the pressures will restore the components back to their original equilibrium positions or distances and could initiate a vibration (oscillation), even a resonance.…”
Section: Methodsmentioning
confidence: 99%
“…Based on published biological and biochemical experimental results [2][3][9][10] , the above analysis, the liquid plasma physics [19] , electrodynamics and hydrodynamics, we propose our model of longitudinal vibrations (oscillations) of free ions in BF, e.g., ions in SR, Cellular Fluid (CF) or Extra Cellular Fluid (ECF) and i.e., directions of the vibrations (oscillations) and the waves propagations are parallel from each other. Figure 1, we consider the SR and the cells as BLPR with Ca++.…”
Section: Longitudinal Vibrations (Oscillations) Of Free Ions In Bfmentioning
confidence: 99%
See 2 more Smart Citations